Giant genital wart in pregnancy: cryotherapy as a spray of hope - Ittigi, Vivekananda; Afshan, Gouhare (International Journal of Research in Dermatology, 2020)
Giant genital warts are caused by (HPV) type 6 and 11. Genital warts in pregnancy pose a treatment challenge. Here we report a case of 19 years pregnant patient treated with cryotherapy. A 19 years mid-term pregnant female presented with complaints of mild itchy increasing growth over the genitalia, in the past 20 days. Examination revealed a pinkish solitary cauliflower like growth over labia majora. The patient was treated with liquid nitrogen cryotherapy with each cycle of freeze and thawing for 15 seconds each for 12 weeks, the lesion almost regressed. Cryotherapy is a safe, easy and effective treatment modality in pregnancy.